PENGARUH PENERAPAN STRATEGI CIRCUIT LEARNING BERBANTUAN LKS TERHADAP PENCAPAIAN KOMPETENSI IPA SISWA KELAS VII SMPN 2 PADANG - Anisa Surya; Yurnetti Yurnetti; Ratnawulan Ratnawulan (Universitas Negeri Padang, 2016)
The problem in this research is not maximal understanding concepts of students science which affect competence achievement of science students. The purpose of this research was to investigated the effect of applying Circuit Learning strategy assisted student worksheet towards the competence achievement of science students grade VII at SMPN 2 Padang. Circuit Learning strategy is a strategy that makes students become more active to exploit the capabilities of thinking so that students gain a better understanding of the materials taught, and this strategy increasing memory of students toward materials that has students understand because the students recording materials that had they understand by connect concepts which they understand in an empty concept maps that have been designed by teachers in their own language. This type of research was Quasi Experimental Research using design of Randomized Control Group Only Design. The population in this research were all students grade VII at SMPN 2 Padang who were registered in the Academic Year of 2015/2016. Sampling was done by purposive sampling technique and cluster random sampling technique. The instrument in this research were competence of cognitive using written tests, competence of affective was measured using observation sheets, and competence of psychomotor was measured using performance assessment sheets. The third hypothesis of competence was analized by using t test at significance level of 0.05. Based on the results, obtained an average value of student learning outcomes of experiment class on the competence of the cognitive, affective and psychomotor are 83.40, 85.97, 87.19. The average value of student learning outcomes in the control class on the competence of cognitive, affective and psychomotor are 79.57, 81.86, 82.94. The results showed the competence of students in the experimental class is higher than the control class. The results of analysis using t test at significance level 0.05 indicates that th > tt, it can be concluded that there are significant effect on the implementation of the Circuit Learning strategy assisted student worksheet towards the competence achievement of science students grade VII at SMPN 2 Padang